THE EFFECTIVENESS OF JOOX APPLICATION IN TEACHING ENGLISH - Nurul Khidayah; Andi Tenri Ampa; hijrah (Journal of Language Testing and Assessment, 2021)
This study aimed to finding the effectiveness of the Joox application in teaching English and students' responses in listening through the Joox application. The researcher applied the pre-experimental method with one-group pre-test and post-test designs, and collected data based on the test. The research sample was the students of class xi Mipa 1 SMAN 1 Tapalang, totaling 26 students. The sample was taken using purposive sampling technique. The results showed that the pre-test results of class XI Mipa 1 students had sufficient value. After treatment and given the post-test, the students' scores increased significantly. The results of this study were the mean value obtained by students through the pre-test was 60.42 and the post-test was 85.38 with the significant value of the paired sample test smaller than the significant level, namely 0.000 <0.05. Then the conclusion of the results of the student interviews shows that 27% of students difficult to listen use the Joox application and 73% of students easy in listening use the Joox application. Based on these results, researchers can conclude that the Joox application is effective in teaching English.